A method for model-independent measurement of the CKM angle β via time-dependent analysis of the B 0 → Dπ + π −, D → K s 0 π + π − decays - A. Bondar (Journal of High Energy Physics, 2018)
Abstract A new method for model-independent measurement of the CKM angle β is proposed, that employs time-dependent analysis of flavour-tagged B 0 → Dπ+π− decays with D meson decays into C P $$ \mathcal{C}\mathcal{P} $$ -specific and K s 0 π + π − final states. This method can be used to measure the angle β with future data from the BelleII and LHCb experiments with the precision level of one degree.